The Foreclosures.com guide to making huge profits investing in pre-foreclosures without selling your soul - McGee, Alexis (John Wiley & Sons, 2007)
This book shows you the most powerful, practical system ever discovered to make money buying pre-foreclosures. If you follow its advice, it could make you rich.